2008
DOI: 10.1002/dvg.20450
|View full text |Cite
|
Sign up to set email alerts
|

Additional molecular support for the new chordate phylogeny

Abstract: Summary: Recent phylogenomic analyses have suggested tunicates instead of cephalochordates as the closest living relatives of vertebrates. In direct contradiction with the long accepted view of Euchordates, this new phylogenetic hypothesis for chordate evolution has been the object of some skepticism. We assembled an expanded phylogenomic dataset focused on deuterostomes. Maximum-likelihood using standard models and Bayesian phylogenetic analyses using the CAT site-heterogeneous mixture model of amino-acid rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
183
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(201 citation statements)
references
References 77 publications
14
183
0
4
Order By: Relevance
“…This is a quite conservative method for sorting genes that aims to detect novelty in the protein sequence space (10,57,62). The number and choice of internodes in the phylogeny are a result of balancing the robustness of these internodes in phylogenetic studies (32,(63)(64)(65)(66)(67)(68), the availability of sequence data for the sequence similarity searches, and the importance of evolutionary transitions (Table S2). Our consensus phylogenies span 16 evolutionary levels (phylostrata) for Arabidopsis thaliana, 18 for Danio rerio, and 20 for Drosophila melanogaster, starting from the origin of cellular organisms (ps1).…”
Section: Methodsmentioning
confidence: 99%
“…This is a quite conservative method for sorting genes that aims to detect novelty in the protein sequence space (10,57,62). The number and choice of internodes in the phylogeny are a result of balancing the robustness of these internodes in phylogenetic studies (32,(63)(64)(65)(66)(67)(68), the availability of sequence data for the sequence similarity searches, and the importance of evolutionary transitions (Table S2). Our consensus phylogenies span 16 evolutionary levels (phylostrata) for Arabidopsis thaliana, 18 for Danio rerio, and 20 for Drosophila melanogaster, starting from the origin of cellular organisms (ps1).…”
Section: Methodsmentioning
confidence: 99%
“…When analyzing phylogenomic datasets, proper modeling of the amino acid substitution process is crucial because the use of overly simplistic models can lead to inaccurate phylogenetic inferences (reviewed in [13][14][15][16][17]. For example, the monophyly of Chordata was not confidently resolved from phylogenomic data until sophisticated substitution models were applied (18,19). The most commonly used models assume the substitution process is the same in all sites of a protein (site-homogeneous) (e.g., 20).…”
Section: Addressing Biases In Phylogenetic Reconstructionmentioning
confidence: 99%
“…Importantly, although chordate topologies may have changed, integrity of the subphylum has been reaffirmed, albeit, perhaps, at the surprising price of destabilizing deuterostomes as a natural group (Delsuc et al, 2008). This point is discussed in this special issue along with the account of challenging morphological and molecular similarities observed between Xenoturbella and Acoelomorph flatworms (Bourlat et al, 2003;Cameron et al, 2000;Delsuc et al, 2008;Philippe et al, 2007;Telford, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…These novel ideas have been subjected to thorough testing and the Olfactores hypothesis has received further support (Bourlat et al, 2006;Delsuc et al, 2006Delsuc et al, , 2008Dunn et al, 2008;Swalla and Smith, 2008). In contrast, the unorthodox assembly of cephalochordates and echinoderms, which initially raised suspicions about chordate monophyly (Delsuc et al, 2006), was not confirmed (Bourlat et al, 2006;Delsuc et al, 2008).…”
Section: Introductionmentioning
confidence: 99%